ACTN1 promotes cell invasion, migration, and EMT in thyroid cancer and is associated with immune infiltration - Song Chen; Xue Luo; Wentai Wang; Xing-hong Chen; Ning Ma; Xue-yin Zhu; Tian Zhou; Qing-jun Gao; Dai-wei Zhao (Scientific Reports)
Abstract Alpha-actin-1 (ACTN1) is a cytoskeletal protein, and new evidence suggests that it is associated with tumor progression and prognosis. However, the expression of ACTN1 in thyroid carcinoma (THCA) and its biological functions are not fully understood. This study aimed to explore the expression and biological function of ACTN1 in THCA. Bioinformatics analysis revealed that ACTN1 was significantly upregulated in THCA and was associated with tumor size, extraglandular invasion, lymph node and distant metastasis, patient prognosis, and immune cell infiltration. qRT-PCR, immunohistochemistry, and western blotting verified the high expression of ACTN1 in the PTC samples. In vitro and in vivo experiments showed that overexpression of ACTN1 promoted THCA cell proliferation, cell cycle, migration, and invasion, and induced epithelial-mesenchymal transition (EMT); knockdown of ACTN1 inhibited these malignant behaviors. Mechanistically, ACTN1 knockdown reduced the phosphorylation levels of PI3K, AKT, and mTOR, whereas its overexpression increased these levels. After treating ACTN1 knockdown cells with the PI3K activator 740Y-P, the invasion and migration ability of the tumor was restored, suggesting that ACTN1 may promote the invasion and migration of THCA by activating the PI3K/AKT/mTOR pathway. In conclusion, ACTN1 is an important regulator of THCA progression and may serve as a potential molecular marker for predicting THCA invasion and metastasis.